Status of Wetland Birds around Hetauda, Makawanpur - Parajuli, Kanchan (International Research Journal of MMC, 2022)
The major objective of this study was to update the status of wetlands birds around Hetauda valley, based on recent observations. The study was conducted in different wetlands and riverine ecosystems of the Hetauda sub-metropolitan city. The present study recorded 81 species of wetland-dependent birds representing 41.9% of the total wetland birds of the country, belonging to nine orders and twenty-three families. Charadriiformes were found to be the most dominant order. Out of the total wetland bird recorded, 36 species were winter visitors, 38 were residents, and seven were summer visitors. It is found to be a good roosting site for many migratory and residential birds. The fishery complex and its adjoining areas were found to be more diverse in comparison to other study sites. Major threat issues observed in the study area are habitat fragmentation and degradation, pollution and sewage from the industrial belts and urban areas, overfishing, poaching, mining of sand and gravel from rivers, lack of awareness, etc. Recently the human activities and population of Hetauda is raising rapidly after the declaration of Hetauda as the capital city of Bagmati province. Furthermore, the important highways of the country like the east-west highway, Tribhuwan highway from Hetauda to Kathmandu, Dharan-Chatara highway, and the Nijgadh-Kathmandu fast track which is under construction are passes through Hetauda. This confirms that Hetauda is rising rapidly and will be converted into a big city soon. So an Instant plan should be developed to ensure sustainable conservation and development in an eco-friendly manner.